NATIONAL SOLID WASTE POLICY DEPLOYMENT: THE CASE OF SETTLEMENT MUNICIPALITIES BETWEEN THE PUBLIC MINISTRY AND SERGIO MOTTA'S HYDROELECTRIC POWER STATION - Amaro, Aurelio Bandeira; Martin, Encarnita Salas [UNESP]; Iacia, Paulo Roberto; Okado, Matheus Naoto Archangelo [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2020)
In the state of Sao Paulo, the Federal and State Public Ministries have filed a lawsuit against Companhia Energetica de Sao Paulo (CESP) due to failure to meet commitments design to mitigate environmental impacts caused by Sergio Motta's Hydroelectric Power Plant. This action led to a fine of $ 119 million earmarked for the 57 western towns of Sao Paulo. Part of these resources were intended for projects involving solid waste management. This article aims to report on implementation of the projects sponsored with resources for solid waste management in the municipalities concerned. To this end, plus a brief background, also describes its main actors, overcoming difficulties and the challenges yet to come. At last, it has been concluded that upon completion of work, waste management should improve significantly in the region, and due to its originality, agreement such as this is a model to be followed by Brazilians legal authorities and perhaps abroad.
Keywords: Court agreement; Sergio Motta HPP; Management of Solid Waste